Implementasi Kegiatan Motorik Berbasis Pembelajaran Tematik: Studi Deskriptif Kualitatif di TK Labschool UPI Tasikmalaya - Ai Firli; Alya Tulhasanah; Ima Siti Rahmawati; Nitha Andinie Martha; Raisya Pasya Purwanto; Yunengsih Nurul Hidayah (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to analyze the implementation of theme-based motor activities at TK Labschool UPI Tasikmalaya, identifying supporting factors, barriers, and their impact on child development. Integrating motor activities into thematic learning is crucial for stimulating holistic development, yet it is often not consistently implemented. This research employed a descriptive qualitative method, collecting data through observation, interviews, and documentation. The subjects included the principal, teachers, and students. The results indicate that gross and fine motor activity programs are systematically designed and integrated into the Weekly Learning Plan (PPM) aligned with specific learning themes. Evaluation is conducted continuously using checklists and anecdotal notes. The findings demonstrate that this approach effectively improves children’s motor skills, self-confidence, and active participation. The program’s success is further supported by strong collaboration between the school and parents. This study recommends the theme-based motor integration model as a reference for Early Childhood Education (ECE) institutions to enhance learning quality